Interaction between gut microbiota and anesthesia: mechanism exploration and translation challenges focusing on the gut-brain-liver axis - Zhang, Ruolan; Li, Li; Yu, Gaojie; Li, Yang; Wei, Kexi; Lin, Liang; Ye, Yifeng (Frontiers in Cellular and Infection Microbiology, 2025)
As a core participant in human metabolism, immunity, and neural regulation, the gut microbiota has been demonstrated to be closely related to anesthesia drug metabolism and perioperative complications in recent years. Via the bidirectional interaction between the gut-brain axis and gut-liver axis, the gut microbiota and its metabolites can regulate central nervous system inflammation, liver drug-metabolizing enzyme activity, and the clearance efficiency of anesthetic drugs. Moreover, anesthetic drugs can significantly reshape the gut microbiota structure by altering intestinal barrier function, inhibiting beneficial bacterial proliferation, or inducing bile acid metabolism disorders, thereby resulting in a vicious cycle of neuroinflammation and metabolic abnormalities. Microbiota-targeted intervention strategies have demonstrated potential in alleviating anesthesia-related complications in response to this interactive network; however, their clinical translation is still limited by incomplete understanding of the underlying mechanisms, individual heterogeneity, and safety challenges. In the future, it will be necessary to integrate multiomics technologies for analyzing the tripartite interaction network of microorganisms, hosts, and drugs, as well as for promoting standardized clinical research, in order to develop individualized anesthesia management plans based on gut microbiota regulation; these initiatives can result in improvements in perioperative safety and patient prognosis.